Традиції козацького рибальського промислу на півдні України. (Zaporizhzhia Historical Review, 2021)
One of the traditional Zaporizhzhyan crafts, fishery, is being investigated in the article. It is shown that the change of owners of Zaporizhzhyan fish estates hadn’t influenced greatly upon the local tradition of fishery.